JAK inhibition and axial spondyloarthritis: new steps on the path to understanding pathophysiology - Ciccia, Francesco; McGonagle, Dennis; Thomas, Ranjeny; Marzo-Ortega, Helena; Martin, David A.; Yndestad, Arne; Volkov, Mikhail (Frontiers in Immunology, 2025)
Axial spondyloarthritis (axSpA) is a chronic inflammatory disease that predominantly affects the sacroiliac joints and spine. Tumor necrosis factor (TNF) and interleukin (IL)-17A are key cytokines in disease pathogenesis and are established axSpA treatment targets. Recently, axSpA treatment options have been complemented by Janus kinase inhibitors (JAKi), which inhibit various cytokines without directly impacting TNF or IL-17 signaling. The effect of JAKi on axSpA remains under investigation: besides a JAK2-mediated (and potentially tyrosine kinase 2 [TYK2]-mediated) effect on the IL-23/IL-17 axis, emerging evidence suggests γδ T cells, type 3 innate lymphoid cells, and mucosa-associated invariant T cells, which are dependent on IL-7 and/or IL-15 and thus on JAK1, are strongly inhibited by JAKi used to treat axSpA. This review summarizes potential effects of JAKi on axSpA and shows evidence from pre-clinical/clinical studies. Greater understanding of the mechanisms of action of available treatments may improve knowledge of axSpA and pave the road for future therapies.